A toughened flame-retardant phenolic resin-based bamboo-plastic composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611396044.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
顶角的有机官能团赋予POSS分子良好的可修饰性和反应性,将其引入酚醛树脂进行物理共混改性,在反应性阻燃剂方面具有潜在的应用前景,但是材料韧性的改良幅度依然并不突出,因此依然难以满足高韧性高阻燃性的使用要求
聚倍半硅氧烷(POSS)是一类具有纳米级笼型Si-O-Si无机骨架、外围有机官能团可灵活设计的有机-无机杂化化合物,可通过改变外围官能团类型(如环氧基、氨基、羟基、乙烯基等)实现与不同聚合物基体的化学结合,其笼型结构可终止基体中微裂纹扩展、Si元素可促进成炭,兼具增韧与阻燃潜力。苯硼酸类化合物是一类含有硼酸基团(-B(OH)2)的功能性小分子,可依据需要引入氨基、羟基、羧基等不同活性官能团;硼酸基团可与含羟基底物(如酚醛树脂及竹粉表面的-OH)形成可逆硼酸酯动态共价键,在外力作用下通过断裂-重组耗散应力,同时B元素协同Si元素提升材料阻燃性。因此,将苯硼酸类化合物通过化学接枝的方式引入POSS表面,制备POSS-g-PBA粉末并引入PF/竹粉体系,该POSS-g-PBA粉末表面的苯硼酸可优先与竹粉表面的羟基和/或酚醛树脂表面的羟基形成可逆硼酸酯动态共价键,而体系中的六次甲基四胺(HMTA)则与热塑性酚醛树脂苯环上的活性氢反应生成亚甲基交联键,二者共同构成共价三维交联网络与动态可逆交联(硼酸酯)并存的双重网络,可同时发挥POSS的增韧与促成炭作用、硼酸酯动态键的应力耗散作用以及B和Si元素的协同阻燃效应,可同步实现复合材料高强度、高韧性与良好阻燃性的统一。
Smart Images

Figure CN122917484A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of polymer composite materials and bamboo-plastic composite materials, and specifically relates to a strong, tough, flame-retardant phenolic resin-based bamboo-plastic composite material, its preparation method, and its application. Background Technology
[0002] Bamboo-plastic composites (BPCs) are renowned for their excellent mechanical properties and lightweight characteristics. Phenolic resin (PF)-based BPCs, in particular, are widely used in building formwork, mechanical components, and vehicle flooring due to their high mechanical strength, heat and corrosion resistance, and intrinsic flame retardancy. However, PF-based BPCs face two major challenges in application: the highly cross-linked three-dimensional network structure formed after phenolic resin curing restricts molecular chain movement, leading to brittleness and a high susceptibility to brittle fracture under stress; and the presence of flammable organic components such as cellulose in bamboo powder significantly reduces the limiting oxygen index (LOI) and weakens the intrinsic flame retardancy.
[0003] To overcome these challenges, researchers attempted to modify PF-based BPCs by adding toughening agents or flame retardants, but the desired results were not achieved. For example, physically blending phenolic resins with rubber-based toughening agents such as nitrile rubber and inorganic flame retardants such as aluminum hydroxide achieved a balance between toughening and flame retardancy to some extent. However, the toughening agent and the resin matrix were only physically compatible, with limited interfacial bonding. Furthermore, the addition of large amounts of inorganic flame retardants easily led to a decrease in mechanical properties, and the synergistic effect between the two needs further improvement. Oligopomerically polyhedral cage-like silsesquioxanes (POSS) possess both inorganic and organic properties, with a hollow cage-like inorganic Si-O-Si framework structure, giving POSS molecules good thermal stability. The organic functional groups at the apex endow POSS molecules with good modifiability and reactivity. Introducing them into phenolic resins for physical blending modification shows potential application prospects in reactive flame retardants. However, the improvement in material toughness is still not significant, thus failing to meet the requirements for high toughness and high flame retardancy. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a tough and flame-retardant phenolic resin-based bamboo-plastic composite material, its preparation method and application, which endows the phenolic resin-based bamboo-plastic composite material with excellent heat resistance and flame retardant properties.
[0005] To solve the above technical problems, the present invention provides a tough and flame-retardant phenolic resin-based bamboo-plastic composite material, which is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 3-15 parts POSS-g-PBA modified powder, 40-80 parts bamboo powder and 3-15 parts hexamethylenetetramine. The POSS-g-PBA modified powder is obtained by using POSS with different functional groups as the matrix skeleton and phenylboronic acid compounds with different functional groups as grafts, and achieving covalent grafting through chemical reaction between the functional groups of the two to obtain POSS-g-PBA modified powder. The different functionalized POSSes are one or more of epoxy POSSes, amino POSSes, hydroxy POSSes, or vinyl POSSes; the different functionalized phenylboronic acid compounds are one or more of aminophenylboronic acid, aldehyde phenylboronic acid, carboxyphenylboronic acid, or mercaptophenylboronic acid.
[0006] Polysilsesquioxanes (POSS) are a class of organic-inorganic hybrid compounds with a nanoscale cage-like Si-O-Si inorganic framework and flexibly designable peripheral organic functional groups. They can chemically bond with different polymer matrices by changing the type of peripheral functional groups (such as epoxy, amino, hydroxyl, and vinyl groups). Their cage-like structure can terminate the propagation of microcracks in the matrix, and Si can promote char formation, exhibiting both toughening and flame-retardant potential. Benzylboronic acid compounds are a class of functional small molecules containing boric acid groups (-B(OH)2). Different active functional groups such as amino, hydroxyl, and carboxyl groups can be introduced as needed. The boric acid groups can form reversible borate ester dynamic covalent bonds with hydroxyl-containing substrates (such as -OH on the surface of phenolic resins and bamboo powder). Under external force, stress is dissipated through fracture-recombination, while B element synergistically enhances the flame retardancy of the material with Si element. Therefore, by introducing phenylboronic acid compounds onto the surface of POSS through chemical grafting, preparing POSS-g-PBA powder, and introducing it into the PF / bamboo powder system, the toughening and char-promoting effects of POSS, the stress dissipation effect of the dynamic bonds of borate esters, and the synergistic flame-retardant effect of B and Si elements can be simultaneously achieved, thus realizing the unity of high strength, high toughness, and good flame retardancy of composite materials.
[0007] This invention uses phenolic resin as a matrix, which not only endows the composite material with good durability and heat resistance, but also enables the construction of dynamic bonds in the borate ester in the system to effectively dissipate energy through the breaking and recombination of dynamic bonds, thereby achieving the toughening of the composite material. The synergy between nano-epoxy POSS and boron compounds further endows the composite material with excellent heat resistance and flame retardant properties.
[0008] Preferably, when the different functionalized POSS is an epoxy POSS, it is matched with aminophenylboronic acid; when the different functionalized POSS is an amino POSS, it is matched with aldehyde phenylboronic acid; when the different functionalized POSS is a hydroxy POSS, it is matched with carboxyphenylboronic acid; when the different functionalized POSS is a vinyl POSS, it is matched with mercaptophenylboronic acid.
[0009] Preferably, the method for preparing POSS-g-PBA modified powder using epoxy-based POSS and aminophenylboronic acid as raw materials includes the following steps: The epoxy-based POSS was preheated by heating, and then diluted with anhydrous tetrahydrofuran or N,N-dimethylformamide to a solid content of about 30wt%~40wt%. Aminophenylboronic acid was added, and the pH was adjusted to 8-9 with triethylamine. The mixture was then magnetically stirred at 60-70°C for 6-12 hours. After concentration, precipitation, washing, and drying, POSS-g-PBA modified powder was obtained. The molar ratio of epoxy POSS to aminophenylboronic acid was 1-3:1-3.
[0010] Preferably, the molar ratio of epoxy group POSS to aminophenylboronic acid is 1:1.2.
[0011] Preferably, it is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts POSS-g-PBA modified powder, 80 parts bamboo powder, and 3 parts hexamethylenetetramine.
[0012] Preferably, the bamboo powder has a particle size of 80 mesh to 120 mesh.
[0013] This invention also provides a method for preparing a strong, tough, and flame-retardant phenolic resin-based bamboo-plastic composite material, comprising the following steps: Weigh out the thermoplastic phenolic resin, POSS-g-PBA modified powder, bamboo powder and hexamethylenetetramine according to the above mass proportions, and mix them evenly to obtain a premix. The premixed material is melt-blended, and the extruded strip is cooled, pelletized or crushed to obtain the composite material raw material; After drying the composite material raw material, it is placed into the mold, and after segmented hot pressing, the pressure is released and the mold is opened to obtain a strong, tough, flame-retardant phenolic resin-based bamboo-plastic composite material. The first stage of hot pressing involves a temperature of 100~120℃, a pressure of 1Mpa~2Mpa, and a duration of 30min~60min; the second stage involves a temperature of 150℃~200℃, a pressure of 5Mpa~10Mpa, and a duration of 30min~120min; the third stage involves depressurization when the temperature is ≤60℃.
[0014] Preferably, the first stage hot pressing temperature is 120℃, the pressure is 1 MPa, and the duration is 30 minutes; the second stage hot pressing temperature is 150℃, the pressure is 10 MPa, and the duration is 60 minutes; the third stage is when the temperature is ≤60℃, the pressure is released.
[0015] This invention also provides the application of a tough and flame-retardant phenolic resin-based bamboo-plastic composite material in building fireproof boards, lightweight automotive components, and interior panels for rail transit vehicles.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: Polysilsesquioxanes (POSS) are a class of organic-inorganic hybrid compounds with a nanoscale cage-like Si-O-Si inorganic framework and flexibly designable peripheral organic functional groups. They can chemically bond with different polymer matrices by changing the type of peripheral functional groups (such as epoxy, amino, hydroxyl, vinyl, etc.). Their cage-like structure can terminate the propagation of microcracks in the matrix, and Si can promote char formation, exhibiting both toughening and flame-retardant potential. Benzylboronic acid compounds are a class of functional small molecules containing boric acid groups (-B(OH)2). Different active functional groups such as amino, hydroxyl, and carboxyl groups can be introduced as needed. The boric acid groups can form reversible borate ester dynamic covalent bonds with hydroxyl-containing substrates (such as -OH on the surface of phenolic resins and bamboo powder). Under external force, stress is dissipated through fracture-recombination, while B element synergistically enhances the flame retardancy of the material with Si element. Therefore, by introducing phenylboronic acid compounds onto the surface of POSS through chemical grafting, POSS-g-PBA powder is prepared and introduced into the PF / bamboo powder system. The phenylboronic acid on the surface of the POSS-g-PBA powder can preferentially form reversible borate ester dynamic covalent bonds with the hydroxyl groups on the surface of bamboo powder and / or the hydroxyl groups on the surface of phenolic resin. Meanwhile, hexamethylenetetramine (HMTA) in the system reacts with the active hydrogen on the benzene ring of thermoplastic phenolic resin to generate methylene crosslinking bonds. Together, they form a dual network of covalent three-dimensional crosslinking network and dynamic reversible crosslinking (borate ester), which can simultaneously exert the toughening and char-promoting effects of POSS, the stress dissipation effect of the dynamic bonds of borate ester, and the synergistic flame-retardant effect of B and Si elements, thus achieving a unity of high strength, high toughness and good flame retardancy in composite materials.
[0017] This invention constructs a crosslinked network containing dynamic covalent bonds of borate esters. These dynamic bonds, upon external impact, can significantly enhance the material's toughness through a fracture-recombination energy-dissipating mechanism, effectively alleviating stress concentration and cracking at the bonding interface, and greatly extending the product's service life. This fundamentally reduces the maintenance and replacement costs of bamboo-plastic composites during long-term service. Simultaneously, the POSS-g-APBA nanostructure synthesized in this invention exhibits extremely high reactivity and dispersibility, requiring only a very small amount to achieve significant toughening and flame-retardant effects, overcoming the high raw material cost burden associated with the large-scale addition of conventional high-end nanomaterials. Attached Figure Description
[0018] Figure 1 This is a diagram illustrating the preparation mechanism of phenolic resin-based bamboo-plastic composite material in Example 1 of the present invention. Detailed Implementation
[0019] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0020] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 15, preferred embodiments are described to avoid redundancy. However, this invention is not limited to these embodiments and can be implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased commercially or prepared using existing methods.
[0021] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0022] Premixed materials can be melt-blended using a twin-screw extruder or a torque rheometer. When using a twin-screw extruder, the temperature is controlled at 130°C–150°C and the speed at 80–120 rpm. When using a torque rheometer, the temperature is set at 150°C and the speed at 60 rpm, with a melt-blending time of 5–10 minutes. The following examples preferably use a torque rheometer for melt-blending of the premixed materials.
[0023] Bamboo powder with a particle size of 80-120 mesh must be dried at 105℃ for 12 hours before use.
[0024] The premixing process described in this invention needs to be carried out in a high-speed mixer or mortar.
[0025] The different functionalized POSSes provided in this invention are one or more of epoxy POSSes, amino POSSes, hydroxy POSSes, or vinyl POSSes; the different functionalized substituted phenylboronic acid compounds are one or more of aminophenylboronic acid, aldehyde phenylboronic acid, carboxyphenylboronic acid, or mercaptophenylboronic acid. When the different functionalized POSSes are epoxy POSSes, they are matched with aminophenylboronic acid; when the different functionalized POSSes are amino POSSes, they are matched with aldehyde phenylboronic acid; when the different functionalized POSSes are hydroxy POSSes, they are matched with carboxyphenylboronic acid; when the different functionalized POSSes are vinyl POSSes, they are matched with mercaptophenylboronic acid. These correspondences exist and can be used to prepare POSS-g-PBA modified powders. The following examples preferably use epoxy POSSes with aminophenylboronic acid, amino POSSes with epoxy EPBA, and hydroxy POSSes with carboxy CPBA.
[0026] Example 1 A tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts POSS-g-PBA modified powder, 80 parts bamboo powder and 3 parts hexamethylenetetramine, wherein the bamboo powder has a particle size of 80~120 mesh and is dried at 105℃ for 12h before use.
[0027] The preparation method of this strong and flame-retardant phenolic resin-based bamboo-plastic composite material includes the following steps: (1) Preparation of epoxy-based POSS-g-amino PBA modified powder The viscous epoxy-based POSS was preheated at 50°C for 15 min to reduce viscosity. It was then diluted with anhydrous tetrahydrofuran (THF) or N,N-dimethylformamide (DMF) to a solid content of approximately 40 wt%. APBA was weighed at a molar ratio of POSS:APBA = 1:1.2 and added to the solution. The pH of the system was then adjusted to 8 with triethylamine to make the system weakly alkaline. The mixed solution was placed in a reaction vessel equipped with a condenser and stirrer, and the reaction was magnetically stirred at 60°C for 12 h.
[0028] After the reaction was completed, most of the solvent was removed by rotary evaporation. The concentrated solution was slowly added dropwise to an excess of frozen anhydrous diethyl ether to precipitate. After filtration, the solution was washed three times with diethyl ether and dried under vacuum at 50°C for 12 hours to obtain a pale yellow POSS-g-PBA modified powder.
[0029] The structure of POSS-g-PBA modified powder can be characterized by infrared spectroscopy: the characteristic peaks of epoxy groups are weakened or disappear, and characteristic absorption peaks related to hydroxyl, amino, BO and Si-O-Si appear, indicating that APBA and epoxy POSS undergo a grafting reaction.
[0030] (2) Preparation of strong and tough flame-retardant phenolic resin-based bamboo-plastic composite materials Weigh out 100 parts by weight of thermoplastic phenolic resin NR, 10 parts by weight of POSS-g-PBA modified powder, 80 parts by weight of bamboo powder, and 3 parts by weight of HMTA. The bamboo powder has a particle size of 80-120 mesh and is dried at 105℃ for 12 hours before use. Premix the above solid components at room temperature in a high-speed mixer or mortar until the color is uniform to obtain a premix.
[0031] The premixed material was added to a torque rheometer and melt-blended at 150℃ and 60r / min for 10min to fully composite the NR, POSS-g-PBA modified powder, and bamboo powder. After cooling, the melt-blended material was pulverized or pelletized and dried in an oven at 80℃ for 2h to obtain the composite molding raw material.
[0032] The composite molding material raw material is loaded into a mold and cured using a segmented hot pressing process: pre-curing at 120℃ and 5MPa for 30 minutes; main curing at 150℃ and 10MPa for 60 minutes; and post-curing at 180℃ and 10MPa for 60 minutes. After hot pressing, the pressure is slowly released and the mold is opened after cooling to below 60℃ to obtain a strong, tough, flame-retardant phenolic resin-based bamboo-plastic composite material.
[0033] The composite material obtained in this example was tested and found to have a flexural strength of 41.7 MPa, a tensile strength of 15.9 MPa, and an impact strength of 2.40 kJ / m². 2 The flexural modulus is 7.68 GPa, and the tensile toughness and fracture energy are 224.3 KJ / m. 3 703.9 J / m 2 It exhibits good overall mechanical properties.
[0034] Example 2 The difference from Example 1 is that the molar ratio of POSS to APBA was adjusted to 1:1 when synthesizing the POSS-g-APBA modified powder, while the rest of the synthesis steps were completely the same as in Example 1.
[0035] A tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts POSS-g-PBA modified powder, 80 parts bamboo powder and 3 parts hexamethylenetetramine, wherein the bamboo powder has a particle size of 80~120 mesh and is dried at 105℃ for 12h before use.
[0036] The preparation method of this strong and flame-retardant phenolic resin-based bamboo-plastic composite material includes the following steps: (1) Preparation of epoxy-based POSS-g-amino PBA modified powder The viscous epoxy-based POSS was preheated at 40°C for 15 min to reduce viscosity. It was then diluted with anhydrous tetrahydrofuran (THF) or N,N-dimethylformamide (DMF) to a solid content of approximately 30 wt%. APBA was weighed at a POSS:APBA molar ratio of 1:1 and added to the solution. The pH of the system was then adjusted to 9 with triethylamine to make the system weakly alkaline. The mixed solution was placed in a reaction vessel equipped with a condenser and stirrer, and the reaction was magnetically stirred at 70°C for 6 h.
[0037] After the reaction was completed, most of the solvent was removed by rotary evaporation. The concentrated solution was slowly added dropwise to an excess of frozen anhydrous diethyl ether to precipitate. After filtration, the solution was washed twice with diethyl ether and dried under vacuum at 50°C for 12 hours to obtain a pale yellow POSS-g-PBA modified powder.
[0038] The structure of POSS-g-PBA modified powder can be characterized by infrared spectroscopy: the characteristic peaks of epoxy groups are weakened or disappear, and characteristic absorption peaks related to hydroxyl, amino, BO and Si-O-Si appear, indicating that APBA and epoxy POSS undergo a grafting reaction.
[0039] (2) Preparation of strong and tough flame-retardant phenolic resin-based bamboo-plastic composite materials Weigh out 100 parts by weight of thermoplastic phenolic resin NR, 10 parts by weight of POSS-g-PBA modified powder, 80 parts by weight of bamboo powder, and 3 parts by weight of HMTA. The bamboo powder has a particle size of 80-120 mesh and is dried at 105℃ for 12 hours before use. Premix the above solid components at room temperature in a high-speed mixer or mortar until the color is uniform to obtain a premix.
[0040] The premixed material was added to a torque rheometer and melt-blended at 150℃ and 60r / min for 5-10 minutes to fully combine NR, POSS-g-PBA modified powder, and bamboo powder. After cooling, the melt-blended material was pulverized or pelletized and dried in an oven at 80℃ for 2 hours to obtain the composite molding raw material.
[0041] The composite molding material raw material is loaded into a mold and cured using a segmented hot pressing process: pre-curing at 120℃ and 5MPa for 30 minutes; main curing at 150℃ and 10MPa for 60 minutes; and post-curing at 180℃ and 10MPa for 60 minutes. After hot pressing, the pressure is slowly released and the mold is opened after cooling to below 60℃ to obtain a strong, tough, flame-retardant phenolic resin-based bamboo-plastic composite material.
[0042] The composite material obtained in this example exhibits a flexural strength of 40.2 MPa, a tensile strength of 15.1 MPa, an impact strength of 2.21 kJ / m², a flexural modulus of 7.31 GPa, and tensile toughness and fracture energy of 211.6 kJ / m³ and 664.8 J / m², respectively. Although these individual properties are slightly lower, the composite material still demonstrates good overall mechanical properties.
[0043] Example 3 A tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 12 parts POSS-g-PBA modified powder, 80 parts bamboo powder and 4 parts hexamethylenetetramine, wherein the bamboo powder has a particle size of 80~120 mesh and is dried at 105℃ for 12h before use.
[0044] The preparation method of this strong and flame-retardant phenolic resin-based bamboo-plastic composite material includes the following steps: (1) Preparation of aminoPOSS-g-aldehyde-modified PBA powder Amino POSS and aldehyde PBA were weighed according to a molar ratio of amino POSS: aldehyde PBA = 1:1.1. The amino POSS was preheated at 50°C for 15 min to reduce viscosity, then dissolved in anhydrous tetrahydrofuran (THF) or N,N-dimethylformamide (DMF) and diluted to a solid content of approximately 35 wt%. Aldehyde PBA was then added, and the reaction system was heated to 70°C under nitrogen protection and magnetically stirred for 8 h. After the reaction was complete, excess deionized water was added to the system, and the mixture was vigorously stirred to precipitate. The precipitate was filtered and washed three times alternately with anhydrous ethanol and deionized water to remove unreacted monomers. The product was vacuum dried at 60°C for 12 h to obtain a white POSS-g-PBA modified powder.
[0045] (2) Preparation of strong and tough flame-retardant phenolic resin-based bamboo-plastic composite materials Weigh out 100 parts by weight of thermoplastic phenolic resin (NR), 12 parts by weight of POSS-g-PBA modified powder, 80 parts by weight of bamboo powder, and 4 parts by weight of HMTA. The bamboo powder has a particle size of 80-120 mesh and is dried at 105℃ for 12 hours before use. Premix the above solid components at room temperature in a high-speed mixer or mortar until the color is uniform to obtain a premix.
[0046] The premixed material was added to a torque rheometer and melt-blended at 150℃ and 60r / min for 10min to fully composite the NR, POSS-g-PBA modified powder, and bamboo powder. After cooling, the melt-blended material was pulverized or pelletized and dried in an oven at 80℃ for 2h to obtain the composite molding raw material.
[0047] The composite molding material raw material is loaded into a mold and cured using a segmented hot pressing process: pre-curing at 120℃ and 5MPa for 30 minutes; main curing at 150℃ and 10MPa for 60 minutes; and post-curing at 180℃ and 10MPa for 60 minutes. After hot pressing, the pressure is slowly released and the mold is opened after cooling to below 60℃ to obtain a strong, tough, flame-retardant phenolic resin-based bamboo-plastic composite material.
[0048] The composite material obtained in this example was tested and found to have a flexural strength of 46.1 MPa, a tensile strength of 19.4 MPa, and an impact strength of 1.62 kJ / m². 2 The flexural modulus is 6.97 GPa, and the tensile toughness and fracture energy are 273.6 KJ / m. 3 916.6 J / m 2 It exhibits good overall mechanical properties.
[0049] Example 4 A tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts hydroxyl POSS-g-carboxylic acid PBA modified powder, 80 parts bamboo powder and 3 parts hexamethylenetetramine, wherein the bamboo powder has a particle size of 80~120 mesh and is dried at 105℃ for 12h before use.
[0050] The preparation method of this strong and flame-retardant phenolic resin-based bamboo-plastic composite material includes the following steps: (1) Preparation of hydroxyl POSS-g-carboxyl PBA modified powder The raw materials were weighed according to the molar ratio of hydroxy POSS to carboxyphenylboronic acid (CPBA) = 1:1.2. Hydroxy POSS was preheated at 50°C for 15 min to reduce viscosity, then dissolved in anhydrous THF with a solid content of approximately 30 wt%, 40 wt%, or 35 wt%. CPBA was added, along with a small amount of p-toluenesulfonic acid as a catalyst. Under nitrogen protection, the temperature was raised to 80°C, and the reaction was magnetically stirred for 10 h. CPBA was covalently grafted onto the POSS surface via esterification between the hydroxyl and carboxyl groups. After the reaction, most of the solvent was removed by rotary evaporation. The concentrated solution was added dropwise to excess anhydrous diethyl ether to precipitate the precipitate. The precipitate was filtered and washed 2-3 times with diethyl ether, then vacuum dried at 60°C for 12 h to obtain a white POSS-g-CPBA modified powder.
[0051] The structure of POSS-g-CPBA can be characterized by infrared spectroscopy: the characteristic peak of hydroxyl groups is weakened, a newly generated ester carbonyl absorption peak appears at about 1730 cm⁻¹, and the characteristic peaks related to B-OH and Si-O-Si are retained, proving that CPBA has been successfully grafted onto the hydroxyl POSS surface.
[0052] (2) The preparation method of the composite material is the same as that in Example 1, but the formula is adjusted to: 100 parts thermoplastic phenolic resin, 10 parts POSS-g-CPBA modified powder, 80 parts bamboo powder, and 3 parts HMTA.
[0053] The composite material obtained in this example has a flexural strength of 44.8 MPa, a tensile strength of 17.2 MPa, an impact strength of 2.15 kJ / m², a flexural modulus of 7.23 GPa, a tensile toughness of 257.4 kJ / m³, and a fracture energy of 832.1 J / m², exhibiting good comprehensive mechanical properties.
[0054] Example 5 The difference from Example 1 is that the amount of POSS-g-APBA modified powder added is adjusted to 15 parts, while the rest of the formulation and process steps are completely the same.
[0055] The composite material obtained in this example exhibits a flexural strength of 39.8 MPa, a tensile strength of 14.7 MPa, an impact strength of 2.18 kJ / m², a flexural modulus of 7.12 GPa, and tensile toughness and fracture energy of 207.5 kJ / m³ and 651.3 J / m², respectively. Compared with Example 1, all properties have decreased. This is because excessive POSS-g-APBA addition can easily lead to local agglomeration in the matrix, forming stress concentration points, resulting in inferior overall mechanical properties compared to Example 1.
[0056] Example 6 The difference from Example 1 is that the amount of POSS-g-APBA modified powder added is adjusted to 5 parts, while the rest of the formulation and process steps are completely the same.
[0057] The composite material obtained in this example exhibits a flexural strength of 38.3 MPa, a tensile strength of 13.8 MPa, an impact strength of 1.89 kJ / m², a flexural modulus of 6.35 GPa, and tensile toughness and fracture energy of 193.2 kJ / m³ and 608.4 J / m², respectively. All these properties are superior to those of Comparative Example 1. However, due to insufficient POSS-g-APBA addition, the toughening and flame-retardant modification effects are weaker than those of Example 1.
[0058] Example 7 The difference from Example 1 is that the amount of POSS-g-APBA modified powder added is adjusted to 3 parts, while the rest of the formulation and process steps are completely the same.
[0059] Example 8 The difference from Example 1 is that a tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts hydroxyl POSS-g-carboxylic acid PBA modified powder, 40 parts bamboo powder and 10 parts hexamethylenetetramine, with the remaining formulation and process steps being completely consistent.
[0060] Example 9 The difference from Example 1 is that a tough and flame-retardant phenolic resin-based bamboo-plastic composite material is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts hydroxyl POSS-g-carboxylic acid PBA modified powder, 50 parts bamboo powder and 15 parts hexamethylenetetramine, with the remaining formulation and process steps being completely consistent.
[0061] Example 10 The difference from Example 1 is that the molar ratio of POSS to APBA is 1:1.
[0062] Example 11 The difference from Example 1 is that the molar ratio of POSS to APBA is 1:2.
[0063] Example 12 The difference from Example 1 is that the molar ratio of POSS to APBA is 1:3.
[0064] Example 14 The difference from Example 1 is that the molar ratio of POSS to APBA is 2:1.
[0065] Example 15 The difference from Example 1 is that the molar ratio of POSS to APBA is 3:1.
[0066] Comparative Example 1: The preparation steps of pure phenolic resin-based bamboo-plastic composite material without the addition of modified POSS are as follows: Weigh out 100 parts by weight of thermoplastic phenolic resin, 80 parts by weight of bamboo powder (80-120 mesh, dried at 105℃ for 12h), and 3 parts by weight of HMTA, and perform premixing, melt blending and hot pressing molding.
[0067] The composite material obtained in this comparative example was tested and found to have a flexural strength of 37.9 MPa, a tensile strength of 12.5 MPa, and an impact strength of 1.33 kJ / m². 2 The flexural modulus is 5.07 GPa, and the tensile toughness and fracture energy are 152.4 KJ / m. 3 478.6 J / m 2 Its overall mechanical properties are far lower than those of Example 1.
[0068] Comparative Example 2: The preparation steps of phenolic resin-based bamboo-plastic composite material modified with only epoxy group POSS are as follows: Weigh out 100 parts by weight of thermoplastic phenolic resin, 10 parts by weight of epoxy POSS, 80 parts by weight of bamboo powder (80-120 mesh, dried at 105 ℃ for 12 h) and 3 parts by weight of HMTA, and premix, melt blend and hot press molding.
[0069] The composite material obtained in this comparative example exhibits a flexural strength of 39.4 MPa, a tensile strength of 13.8 MPa, an impact strength of 1.68 kJ / m², a flexural modulus of 5.63 GPa, and tensile toughness and fracture energy of 168.3 kJ / m². 3 527.5J / m 2 Compared to Comparative Example 1, there is an improvement, but since POSS is directly mixed in without grafting modification, its dispersibility in the matrix is limited, and the modification effect is weaker than that of Example 1.
[0070] Comparative Example 3: The preparation steps of phenolic resin-based bamboo-plastic composite material modified with only aminophenylboronic acid are as follows: Weigh out 100 parts by weight of thermoplastic phenolic resin, 3 parts by weight of aminophenylboronic acid (APBA), 80 parts by weight of bamboo powder (80-120 mesh, dried at 105℃ for 12h), and 3 parts by weight of HMTA, and premix, melt blend and hot press molding.
[0071] The composite material obtained in this comparative example exhibits a flexural strength of 38.6 MPa, a tensile strength of 13.5 MPa, an impact strength of 1.91 kJ / m², a flexural modulus of 5.41 GPa, and tensile toughness and fracture energy of 179.6 kJ / m³ and 561.2 J / m³, respectively. 2 The boric acid groups in APBA can form dynamic borate bonds with the hydroxyl groups on the surface of phenolic resin and bamboo powder, which contributes to toughness. However, APBA small molecules are prone to migration and aggregation in the matrix, resulting in limited dispersion uniformity. Furthermore, they lack stable covalent binding sites with the matrix, making the modification effect weaker than that in Example 1.
[0072] The above Examples 1 to 15 can all prepare strong and tough flame-retardant phenolic resin-based bamboo-plastic composite materials. The performance of the strong and tough flame-retardant phenolic resin-based bamboo-plastic composite materials prepared in Examples 1 to 6 is now preferred for verification.
[0073] Experimental Test (1) Mechanical properties According to standard GB / T29418-2023, tensile strength, three-point bending strength and impact toughness tests were conducted on the bamboo-plastic composite molded specimens of Comparative Examples 1-3 and Examples 1-6, respectively. The results are shown in Table 1.
[0074] Table 1 Mechanical properties of bamboo-plastic composite molded specimens Comparing the three comparative examples, it can be found that the mechanical properties of Comparative Example 2 (with only epoxy-based POSS) and Comparative Example 3 (with only APBA) are superior to those of Comparative Example 1 (blank control), indicating that both the POSS cage structure and the borate ester dynamic bonds in APBA contribute to the modification of the composite material. The impact strength of Comparative Example 3 is slightly higher than that of Comparative Example 2, indicating that the borate ester dynamic bonds introduced by APBA contribute more significantly to the dissipation of impact energy; while the flexural modulus of Comparative Example 2 is slightly higher than that of Comparative Example 3, indicating that the POSS cage structure contributes more to improving the rigidity of the system. However, the modification effects of both are weaker than those of the other examples. This is because when POSS and APBA are directly mixed in alone, they suffer from insufficient dispersibility or a lack of stable covalent bonding sites, thus failing to exert their synergistic modification effect.
[0075] Of the various embodiments, Embodiment 1 exhibited the highest impact strength, reaching 2.40 kJ / m². 2 Example 3 showed the most outstanding performance in terms of tensile strength, flexural strength, tensile toughness, and fracture energy (916.6 J / m²). The overall mechanical properties of all examples were significantly better than those of the comparative examples. The main reasons are as follows: First, the POSS-g-PBA modified powder fixes phenylboronic acid compounds to the POSS surface through covalent grafting, which solves the agglomeration problem when POSS is directly mixed in, and makes it uniformly dispersed in the phenolic resin matrix. The POSS cage structure can effectively terminate the propagation of microcrack tips in the matrix and induce crazes, dissipating impact energy and achieving toughening. Second, the phenylboronic acid groups grafted to the POSS surface can form reversible borate ester dynamic covalent bonds with the abundant hydroxyl groups on the surface of phenolic resin and bamboo powder. Under the action of external force, the dynamic bonds further dissipate stress and inhibit crack propagation through a reversible fracture-reorganization mechanism, which synergistically enhances the toughening effect of the POSS cage structure and improves the overall mechanical properties of the composite material.
[0076] The performance of Example 1 is superior to that of Example 2, indicating that appropriately increasing the molar ratio of APBA to POSS is beneficial to improving the grafting rate, introducing more borate ester dynamic bonds, and resulting in a more significant toughening effect. The overall mechanical properties of Examples 5 and 6 are both inferior to those of Example 1, indicating that the mechanical properties first increase and then decrease with the increase of POSS-g-APBA content. Insufficient addition results in limited modification effect, while excessive addition easily leads to local agglomeration in the matrix, forming stress concentration points and weakening the overall mechanical properties.
[0077] (2) Flame retardant properties The combustion behavior of the bamboo-plastic composite materials obtained in Comparative Examples 1-3 and Examples 1-6 was evaluated using the cone calorimetry method, and the results are shown in Table 2.
[0078] Table 2 Mechanical properties of bamboo-plastic composite molded specimens As shown in Table 2, compared with Comparative Example 1 without the modifier, all examples with the addition of POSS-g-APBA exhibited superior flame retardant properties. Among them, Example 5 showed the best overall flame retardant effect, with a limiting oxygen index of 38.5%, a peak heat release rate (pHRR) reduced to 195.94 kW·m⁻², and a total heat release (THR) reduced to 53.74 MJ·m⁻². Compared with Comparative Example 1, pHRR and THR were reduced by approximately 46.8% and 44.5%, respectively, indicating that POSS-g-APBA modification can effectively suppress heat release during the combustion process of the composite material.
[0079] Comparative Examples 2 and 3, with the addition of POSS and APBA respectively, showed superior flame-retardant performance compared to Comparative Example 1, indicating that both Si and B elements can play a certain flame-retardant role. Specifically, the Si-O-Si inorganic structure in POSS promotes the formation of a silicon-containing protective layer, improving char layer stability; while the boron element in APBA promotes the dehydration and carbonization of cellulose and resin components, enhancing char formation ability. However, due to the lack of effective synergistic effect when either exists alone, their flame-retardant effect is still lower than that of the POSS-g-APBA modified system.
[0080] The superior flame-retardant properties of the POSS-g-APBA modified system are primarily due to two factors: Firstly, the Si element in the POSS cage structure promotes the formation of a dense silicon-containing protective layer during combustion, hindering heat transfer and oxygen diffusion. Secondly, the Bo element in APBA promotes char formation and, together with Si, forms a stable Si / B synergistic char layer structure. Furthermore, POSS-g-APBA improves the dispersibility of the modified components in the phenolic resin matrix through chemical grafting, allowing the flame-retardant elements to be uniformly distributed within the material, thus achieving sustained flame retardancy.
[0081] It is worth noting that although the ignition time (TTI) of Examples 1 and 3 was lower than that of Comparative Example 1, their pHRR and THR were significantly reduced, and the char residue was significantly improved. This is because POSS-g-APBA can promote early dehydration and carbonization of the material, rapidly forming a protective char layer in the early stage of combustion, thereby inhibiting subsequent heat release. Therefore, the reduction in TTI does not represent a decrease in overall flame retardant performance, but rather reflects the material's transformation from a "delayed combustion" to a "rapid char formation and protection" combustion mode.
[0082] Epoxy-based POOS is first grafted with aminophenylboronic acid under alkaline conditions to prepare POSS-g-PBA modified powder. Then, the modified POSS-g-PBA powder is blended with bamboo fiber, thermoplastic phenolic resin and hexamethylenetetramine until homogeneous. Then, it is hot-pressed. Under the action of heat, the phenylboronic acid and hexamethylenetetramine on the surface of POSS-g-PBA powder undergo cross-linking reactions with the hydroxyl groups on the surface of thermoplastic phenolic resin to generate dynamic borate ester bonds (breakage and recombination consume energy) and methylene covalent bonds to form a three-dimensional cross-linked network. (The phenylboronic acid on the surface of POSS-g-PBA powder forms reversible borate ester dynamic covalent bonds with the hydroxyl groups on the surface of bamboo powder and / or the hydroxyl groups in the molecular structure of phenolic resin, while the hexamethylenetetramine (HMTA) in the system reacts with the active hydroxyl groups on the benzene ring of thermoplastic phenolic resin to generate methylene cross-linking bonds. The two together constitute a dual network of covalent three-dimensional cross-linked network and dynamic reversible cross-linking (borate ester), which endows the composite material with good mechanical strength, toughness and flame retardant properties.
[0083] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A tough, flame-retardant phenolic resin-based bamboo-plastic composite material, characterized in that, It is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 3-15 parts POSS-g-PBA modified powder, 40-80 parts bamboo powder and 3-15 parts hexamethylenetetramine; The POSS-g-PBA modified powder is obtained by using POSS with different functional groups as the matrix skeleton and phenylboronic acid compounds with different functional groups as grafts, and achieving covalent grafting through chemical reaction between the functional groups of the two to obtain POSS-g-PBA modified powder. The different functionalized POSSes are one or more of epoxy POSSes, amino POSSes, hydroxy POSSes, or vinyl POSSes; the different functionalized phenylboronic acid compounds are one or more of aminophenylboronic acid, aldehyde phenylboronic acid, carboxyphenylboronic acid, or mercaptophenylboronic acid.
2. The strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 1, characterized in that, When the functionalized POSS is an epoxy POSS, it is matched with aminophenylboronic acid; when the functionalized POSS is an amino POSS, it is matched with aldehyde phenylboronic acid; when the functionalized POSS is a hydroxy POSS, it is matched with carboxyphenylboronic acid; when the functionalized POSS is a vinyl POSS, it is matched with mercaptophenylboronic acid.
3. The strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 1, characterized in that, The preparation method of POSS-g-PBA modified powder using epoxy-based POSS and aminophenylboronic acid as raw materials includes the following steps: The epoxy-based POSS was preheated by heating, and then diluted with anhydrous tetrahydrofuran or N,N-dimethylformamide to a solid content of about 30wt%~40wt%. Aminophenylboronic acid was added, and the pH was adjusted to 8-9 with triethylamine. The mixture was then magnetically stirred at 60-70°C for 6-12 hours. After concentration, precipitation, washing, and drying, POSS-g-PBA modified powder was obtained. The molar ratio of epoxy POSS to aminophenylboronic acid was 1-3:1-3.
4. The strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 3, characterized in that, The molar ratio of epoxy-based POSS to aminophenylboronic acid is 1:1.
2.
5. The strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 1, characterized in that, It is made from the following raw materials in parts by weight: 100 parts thermoplastic phenolic resin, 10 parts POSS-g-PBA modified powder, 80 parts bamboo powder and 3 parts hexamethylenetetramine.
6. The strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 1, characterized in that, The bamboo powder has a particle size of 80-120 mesh.
7. The method for preparing the strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to any one of claims 1 to 6, characterized in that, Includes the following steps: Weigh out the thermoplastic phenolic resin, POSS-g-PBA modified powder, bamboo powder and hexamethylenetetramine according to the above mass proportions, and mix them evenly to obtain a premix. The premixed material is melt-blended, and the extruded strip is cooled, pelletized or crushed to obtain the composite material raw material; After drying the composite material raw materials, they are placed into a mold, and after segmented hot pressing, the pressure is released and the mold is opened to obtain phenolic resin-based bamboo-plastic composite material. The first stage of hot pressing involves a temperature of 100~120℃, a pressure of 1Mpa~2Mpa, and a duration of 30min~60min; the second stage involves a temperature of 150℃~200℃, a pressure of 5Mpa~10Mpa, and a duration of 30min~120min; the third stage involves depressurization when the temperature is ≤60℃.
8. The method for preparing the strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 7, characterized in that, The first stage of hot pressing is at a temperature of 120℃ and a pressure of 1 MPa for 30 minutes; the second stage of hot pressing is at a temperature of 150℃ and a pressure of 10 MPa for 60 minutes; the third stage involves depressurization when the temperature is ≤60℃.
9. The application of the strong and tough flame-retardant phenolic resin-based bamboo-plastic composite material according to claim 1 in fireproof building panels, lightweight automotive components, and interior panels for rail transit vehicles.